Evaporation‐driven octagonal particle deposition on the patterned substrate - Si X. Lim; Junheng Ren; Kian‐Soo Ong; Karen S. L. Chong; Fei Duan (Droplet, 2022)
Abstract Understanding noncircular deposition patterns can offer broad applications; however, the phenomena have not been thoroughly studied. We experimentally investigate particle self‐assembly of microspherical polystyrene particle‐laden sessile droplets dried on a micropyramid cavity substrate. The particle sizes and concentrations in the droplets are found to modify the inner particle deposition with the octagonal perimeter. The droplets with mass concentrations of 0.5% and higher evaporate with the pinned contact lines. The capillary flow flushes the 3 µm particles to the contact line and creates octagonal outer‐ring patterns. The 10 µm particles are more evenly distributed in the depositions of the dried droplets. However, at a high mass concentration of 2.6%, the particles adsorbed at the droplet liquid–air interface form an agglomerate and deposit toward the centerline, leading to the crater‐shaped pattern. Higher concentrations provoke the thicker octagonal outer‐ring depositions regardless of the particle sizes in the droplets. The findings could inspire applications to control noncircular wetting and drying of particle‐laden sessile droplets.